PEMERIKSAAN MRI PELVIS WANITA DENGAN KLINIS ENDOMETRIOSIS - Sriyatun, Sriyatun; Sari, Gando; Maulana Budianto, Rudi; Heriyanto, Heriyanto; Pramono, Pramono; Darmiyeti, Darmiyeti (Perhimpunan Radiografer Indonesia (PARI), 2020)
Introduction: The pelvic anatomy is an ideal part of using Magnetic Resonance Imaging (MRI) as it is particularly suitable for detecting abnormalities in soft tissues. Endometriosis is a disease that is 10% suffered by women in the premenopausal or reproductive period, in which a tissue that resembles endometrium outside the uterus is purely a chronic inflammatory action. Materials and Methods: This research is descriptive qualitative with case study approach. MRI Pelvic Women Examination with clinical Endometriosis using protocol sequences: T2 TSE and T1 SPAIR sagittal planes; T2 TSE long axis (LAX) and short axis (SAX); T1 TSE; T1 FLAIR, T1 TSE FS, EP2D Diffusion axial planes; as well as the T2 Haste FS of coronal planes thick slice and T2 Spc3D sequences. Results and Discussion: In the outcome of the images seen cyst endometriosis in the right-left ovarium, hypointense on T2 and hyperintense on T1 and T1 FS. Enlarged uterine size. Seen multiple cysts of hypointense posterior uterine lesions in sequence T2 and hyperintens in sequence T1 SPAIR.Conclusions: MRI Pelvic Women Examination have a good role to diagnose the pathologies of female genetic organs and the anatomy between organs can be clearly distinguished by the giving of vaginal and rectum ultrasound jelly, and full bladder.